Intradialytic hypotension in acute kidney injury requiring renal replacement therapy. Issue 6 (30th June 2017) - Sharma, Shilpa; Waikar, Sushrut S.
Abstract: The treatment of severe acute kidney injury (AKI) with dialytic support for renal replacement therapy can be life sustaining and permit recovery from critical illness. Like any interventional therapy, however, renal replacement therapy with intermittent hemodialysis or continuous therapy can cause complications. Intradialytic hypotension is a common complication and can cause further ischemic injury to the recovering kidneys, thereby reducing the probability of renal recovery. The optimal dialytic technique—continuous or intermittent—has not been conclusively demonstrated in randomized controlled trials. In general, treatment or prophylactic strategies for intradialytic hypotension in AKI have not been comprehensively tested. Given the frequency of intradialytic hypotension in dialytic treatment of AKI and its adverse clinical consequences, future research should rigorously compare dialytic techniques and other prevention strategies in adequately powered, randomized controlled trials.